Power and performativity in prison: exploring male sex workers' experiences and performances of gender and sexuality pre/during/post-incarceration - Lewin, Jan-Louise (Gender Studies, 2018)
This study explores the narratives of men who become male sex workers after being in prison. This study looks at prison as a fluid space for sexual expression and gender performativity, which is ironic given the view of prison as punitive and repressive. Sex within the South African prison system is silenced and taboo particularly within the Number prison gang where sex is heavily regulated, ritualized and fiercely guarded. The research question asks how do men who are or become male sex workers construct and perform their gendered and sexual identities in prison and on the street? This qualitative study employs the organizing metaphor of dramaturgy to explore how prison as a social setting (stage) impacts on the gendered and sexual performances of men (actors) who have been incarcerated. Drawing on Foucault's theories of the repressive hypothesis and peripheral sexualities (1990), Butler's theory of performativity (1990) and Gagnon and Simon's scripting theory (1973) this study illustrates theoretically how prison sex culture and male sex work can be theorized from a feminist standpoint perspective. This feminist study is located in the social constructionist paradigm. It is underpinned by grounded theory and narrative methodology to explore the narratives of men who have been incarcerated and continue into sex work post-release. Biographical interviews were conducted with 15 men who were participants in a male sex work support group. Findings revealed two overarching themes in the narratives that explain how men construct and perform their gendered and sexual identities in prison. Renegotiation was the process where the subject engaged in an internalized monologue with self, constantly exploring and (re)constructing the gendered and sexual self in response to the shifting contexts of prison and the streets. Negotiation was the process where the subject engaged in an external dialogue with others. Through interactions with others, they were able to perform gender and sexuality publicly. By framing it within the discourse of dramaturgy, this study shows an alternative view of prison sex culture. (Re)imagining prison as the 'stage', prisoners as the 'actors', prison rituals as the 'script' and identity performances as the 'act', we can begin to envision an alternative script and narrative of prison unfolding.